Dehumanization during Delivery: Meanings and Experiences of Women Cared for in the Medellín Public Network - Cristina María Mejía Merino (Investigación y Educación en Enfermería, 2018)
Objective This work sought to describe the meanings constructed in the experiences of women in relation to the care received by the healthcare staff at the moment of delivery. Methods Qualitative study using the procedures proposed by the Grounded theory for data analysis. The sample comprised 18 women over 14 years of age, between 40 days and 6 months postpartum. Twelve of the participants were selected through convenience and to reach saturation of the categories, six more participants were included by using theoretical sampling. Semi-structured interviews were conducted in three information collection phases, and said interviews were analyzed line by line by using coding and categorization techniques. Results The mothers described the parturition experience negatively, perceiving it as the implicit imposition of stoicism to repress their emotions, pain, and discomfort and prefer an attitude of submission to the health staff. The participating mothers critically conjure up the care received, which translates into procedures performed and verbal and psychological abuse. Conclusion The mothers assign meanings to their experiences of the delivery process not so much as a transcendent human experience, but rather as a super-experience to the dehumanization of giving birth within the biomedical context.